2016
DOI: 10.1016/j.aca.2015.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Novel CeO2–CuO-decorated enzymatic lactate biosensors operating in low oxygen environments

Abstract: The detection of the lactate level in blood plays a key role in diagnosis of some pathological conditions including cardiogenic or endotoxic shocks, respiratory failure, liver disease, systemic disorders, renal failure, and tissue hypoxia. Here, we described for the first time the use of a novel mixed metal oxide solution system to address the oxygen dependence challenge of first generation amperometric lactate biosensors. The biosensors were constructed using ceria-copper oxide (CeO2-CuO) mixed metal oxide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…oxidation current graph is shown in Figure 4a. It was found that the oxidation current of Pt/CeO2-TiO2/LOx/Nf sensors measured at 0.8 V increased linearly with the increasing scan rate as shown in Figure 4b, demonstrating that the oxidation of H2O2 on the surface of the sensor is a surface controlled electrochemical reaction (9).…”
Section: L-lactate + O2 → Pyruvate + H2o2mentioning
confidence: 87%
See 1 more Smart Citation
“…oxidation current graph is shown in Figure 4a. It was found that the oxidation current of Pt/CeO2-TiO2/LOx/Nf sensors measured at 0.8 V increased linearly with the increasing scan rate as shown in Figure 4b, demonstrating that the oxidation of H2O2 on the surface of the sensor is a surface controlled electrochemical reaction (9).…”
Section: L-lactate + O2 → Pyruvate + H2o2mentioning
confidence: 87%
“…The results showed that the chemical modification of CeO2 nanostructures enhanced the electrochemical performance significantly. In our previous works, we demonstrated that the modification of CeO2 lattice with a second metal oxide system altered the physicochemical properties of the nanoparticles, which in turn resulted in an enhanced catalytic performance (9,10,24).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that CeO 2 -CuO mixed oxide nanomaterials were promising nanocatalysts for the preferential oxidation of CO [14]. Copper oxide nanomaterials are applied in various areas: gas sensors [15], biosensors [16], batteries [17], high temperature superconductors [18], solar energy conversion [19], field emission emitters [20], and catalysis [21]. It has been reported that the efficiency of CeO 2 -CuO nanocatalysts could be related to synergetic interactions between CeO 2 and CuO promoting special redox properties at their interface [22].…”
Section: Introductionmentioning
confidence: 99%
“…CuO monoklinik kristal yapıya sahip, zehirli olmayan, ucuz, kolay sentezlenebilen ve doğada bol bulunan bir yarıiletken malzemedir. Bu yüzden CuO ince filmler biyosensörler [5], gaz sensörleri [6], güneş pilleri [7], lityum iyon bataryalar [8], ince film transistörler [9] gibi teknolojinin birçok alanında değişik uygulamalar için yaygın biçimde araştırılmaktadır.…”
Section: Gi̇ri̇ş (Introduction)unclassified